CAPITAL STRUCTURE AND FIRM PERFORMANCE OF LISTED MANUFACTURING FIRMS IN NIGERIA STOCK EXCHANCE - OLANIYI, Rafiyat Bosede; ABILORO, Kayode Peter; OLANIYAN, Niyi Oladipo (Annals of Spiru Haret University. Economic Series, 2022)
This research studied the link between capital structure and financial performance of Nigerian manufacturers. It evaluated the nexus between total debt and financial performance of listed manufacturing companies in Nigeria, the nexus between equity and financial performance of listed manufacturing firms in Nigeria.Stock Exchange. The study used ex-post-facto data to investigate variable relationships. Nigerian manufacturing firms were studied. The data was taken from the company's (2005-2020). Both descriptive and inferential statistics, such as Pearson correlation and panel regression, were used to examine the data. Return on equity, equity capital has a substantial influence on the performance of Nigerian manufacturing companies. 6.34 and 0.26 Total debt assessed by asset debt-to-equity ratio has no influence on stock market performance (p>0.6580). Sand return on equity has a positive significant influence on financial performance of Nigerian manufacturing firms by 6.331 (p=0.0000.05) and 0.117 (p=0.0070.05); long-term debt also has a positive significant effect. The study found that equity capital, total debt, and long-term debt have the potential to positively and significantly influence the financial performance of manufacturing firms in Nigeria, whereas short term debt has the potential to positively and insignificantly influence financial performance. Total asset has the potential to positively and significantly influence financial performance.